2003
DOI: 10.1074/jbc.m300336200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-like Fibril Formation in an All β-Barrel Protein

Abstract: Acidic fibroblast growth factor from newt (Notopthalmus viridescens) is a ϳ15-kDa, all ␤-sheet protein devoid of disulfide bonds. In the present study, we investigate the effects of 2,2,2-trifluoroethanol (TFE) on the structure of newt acidic fibroblast growth factor (nFGF-1). The protein aggregates maximally in 10% (v/v) TFE. Congo red and thioflavin T binding experiments suggest that the aggregates induced by TFE have properties resembling the amyloid fibrils. Transmission electron microscopy and x-ray fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 52 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…In addition to be a cosolvent commonly used to promote amyloid formation (20,27,28), TFE has also proven useful for revealing details of the mechanism of protein aggregation (29 -31). For the study of aggregation of Sso AcP, we focused on the first aggregational events, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to be a cosolvent commonly used to promote amyloid formation (20,27,28), TFE has also proven useful for revealing details of the mechanism of protein aggregation (29 -31). For the study of aggregation of Sso AcP, we focused on the first aggregational events, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…19 Likewise, the promotion of aggregation-prone folding intermediates has been observed in a limited range of alcohol concentrations, as has been shown, for instance, for the Alzheimer b-protein, 20 for a-synuclein 21 and for the acidic fibroblast growth factor. 22 These observations point to the importance of considering the interplay between various, eventually antagonistic, solvational effects on protein aggregation, in the particular case of alcohols as cosolvents.…”
Section: Introductionmentioning
confidence: 97%
“…Srisailam et al [111] reported that the acidic fibroblast growth factor from Notopthalmus viridescens is able to form amyloid like fibrils. This demonstrated that -barrel proteins could also be forced to form amyloid-like fibrils, supporting the notion that fibrils formation is an intrinsic property of many if not all proteins.…”
Section: Discussionmentioning
confidence: 98%